2021
DOI: 10.1080/15459624.2021.1948047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sampling and storage stress on the recovery of airborne SARS-CoV-2 virus surrogate captured by filtration

Abstract: Environmental air sampling of the SARS-CoV-2 virus in occupational and community settings is pertinent to reduce and monitor the spread of the COVID pandemic. However, there is a general lack of standardized procedures for airborne virus sampling and limited knowledge of how sampling and storage stress impact the recovery of captured airborne viruses. Since filtration is one of the commonly used methods to capture airborne viruses, this study analyzed the effect of sampling and storage stress on SARS-CoV-2 sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…After sampling, all filters were refrigerated before transport to the laboratory. Previous research 49 showed no significant change in viral recovery with filter storage at 4°C for up to 1 week. Field and laboratory blanks were processed periodically during the study, accounting for 10% of the total samples.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…After sampling, all filters were refrigerated before transport to the laboratory. Previous research 49 showed no significant change in viral recovery with filter storage at 4°C for up to 1 week. Field and laboratory blanks were processed periodically during the study, accounting for 10% of the total samples.…”
Section: Methodsmentioning
confidence: 74%
“…The elution protocol of virus‐associated particles from a PTFE filter was optimized previously using a SARS‐CoV‐2 surrogate virus, Human Coronavirus OC43. 49 Briefly, the filter sample was placed in a microcentrifuge tube with 1 ml sterile RNA‐free water (ThermoFisher Scientific) and vortexed three times for 10 s each. The eluate was then used for RNA extraction and analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation